2023
DOI: 10.3389/fmed.2023.1295299
|View full text |Cite
|
Sign up to set email alerts
|

Latent tuberculosis infection (LTBI) in health-care workers: a cross-sectional study at a northern Peruvian hospital

Edinson Dante Meregildo-Rodriguez,
Verónica Yuptón-Chávez,
Martha Genara Asmat-Rubio
et al.

Abstract: BackgroundHealthcare workers (HCWs) have a higher risk of latent tuberculosis infection (LTBI) and active tuberculosis than the general population. In HCWs, the risk of tuberculosis infection depends on the local tuberculosis prevalence, HCWs’ characteristics, the healthcare facility, and prevention and control measures. We aimed to estimate the prevalence and risk factors for LTBI in HCWs at a northern Peruvian hospital.MethodsThis study had two phases: (1) a cross-sectional phase involving recruitment, histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Overall, the variation in infection may involve the result of compliance with protective measures for infection control. Regarding employment duration, our finding on the impact of working time was similar to the previous study and systematic review reports on LTBI among HCWs which found the association of TB infection with the length of time working in healthcare facilities [ 13 , 26 , 30 ]. This effect can be explained by the longer working time increasing exposure to TB and, consequently, increasing the risk of acquiring TB infection.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Overall, the variation in infection may involve the result of compliance with protective measures for infection control. Regarding employment duration, our finding on the impact of working time was similar to the previous study and systematic review reports on LTBI among HCWs which found the association of TB infection with the length of time working in healthcare facilities [ 13 , 26 , 30 ]. This effect can be explained by the longer working time increasing exposure to TB and, consequently, increasing the risk of acquiring TB infection.…”
Section: Discussionsupporting
confidence: 89%
“…Univariate and multivariate analyses were performed using logistic regression to assess the association between possible risk factors and QFT-Plus positive results. Several factors may increase the risks of acquiring TB infection, and the risks of LTBI differ among HCWs depending on local TB prevalence, healthcare facilities, and infection prevention and control measures [ 26 ]. Different risk factors for LTBI in HCWs were reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations